The combination of Lactobacillus sp. and turmeric flour (Curcuma longa) in feed on growth, feed conversion and survival ratio of Litopenaeus vannamei Boone, 1931 - Akhmad Mulyadi; Iin Siti Djunaidah; Sinung Rahardjo; Agung Setia Batubara (Depik, 2022)
White shrimp (Litopenaeus vannamei) cultivation activities have developed rapidly in Indonesia. White shrimp aquaculture which is carried out intensively with high stocking densities has caused several problems, such as low survival and suboptimal growth. This study aimed to increase the growth, feed conversion, and survival of white shrimp through a combination of probiotics (Lactobacillus sp.) + turmeric flour (Curcuma longa) in feed. The method used in this study was Completely Randomized Design (CRD) with four treatment levels and three replications. The results revealed a significant effect (P0.05) on the value of the daily growth rate (DGR), absolute growth rate (AGR), specific growth rate (SGR), survival rate (SR), feed conversion ratio (FCR), and feed efficiency (FE), but no significant effect (P0.05) on the value of the absolute length rate (ALR). Giving probiotics 10 ml+5 g turmeric flour/kg feed (treatment B) was the best treatment for white shrimp aquaculture, including DGR, AGR, ALR, LPS, SR, FCR, and FE values. Furthermore, the results also revealed that increasing the concentration of turmeric flour in the feed, was negatively correlated to the growth and survival of white shrimp.